Inoculation of nitrogen-fixing halobacteria in the contribution to tolerance to salt stress in bean tepary (Phaseolus acutifolius) - Renganathan, Prabhaharan; Borboa-Flores, Jesús; Rosas-Burgos, Ema Carina; Cárdenas-López, José Luis; Murillo-Amador, Bernardo; Ortega-García, Jesús; Rueda-Puente, Edgar Omar (Revista Mexicana de Ciencias Agrícolas, 2018)
Drought tolerant tepary bean (Phaseolus acutifolius A. Gray) is a microbiologically unexplored culture in arid regions of Mexico where it is consumed as a source of dietary protein. However, soil salinity hinders the productivity of this crop. The isolation of specific halotolerant nitrogen-fixing bacteria (BFN) could be a novel practice to improve salt tolerance and improve crop productivity. In the present study, 24 BFN were isolated from seeds of three tepary ecotypes exposed to high salinities (0, 0.25 and 0.5 M NaCl) in vitro. Nitrogen-fixing halotolerant strains were characterized. Among the halotolerant isolates, only one showed high nitrogenous activity of 6.97 ± 1.1 nmol of culture-1 h-1. From the 16S analysis of rRNA, the halotolerant microorganism exhibited 99% sequence homology with the known bacterium Bacillus amyloliquefaciens. The results show that the inoculation with the identified halotolerant isolate had stimulating effects on growth parameters, seed germination, seed emergence, shoot length, root length, biomass, foliar chlorophyll and protein content, ash and crude fibers.